COMPARATIVE STUDY OF POLYPHENOLS FROM PROPOLIS EXTRACTS OF DIFFERENT ORIGIN - DĂRĂBAN, Adriana; OLAH, Neli Kinga; CÂMPEAN, Ramona Flavia; FURTUNA, Flavia; COBZAC, Codruta; DEHELEAN, Gheorghe; BOJIȚĂ, Marius; HANGANU, Daniela (Studia Universitatis Babeș-Bolyai Chemia, 2015)
The propolis, a resinous substance produced by bees, was used from ancient times as one of the best general panaceea. The main active compounds known in propolis are the phenolic acids and flavonoids from the class of polyphenols. This paper presents the flavonoids and phenolic acids evaluation by chromatographic (TLC and HPLC) methods of some propolis samples originating from Arad (4 samples) and Bihor (3 samples) counties, from west of Romania. There were identified the caffeic, ferulic and gallic acids respectively the chrysine and kaempferol. The chrysine content ranges from 0.15 to 1.95 mg/ml and the kaempferol from 0.07 to 8.88 mg/ml. The caffeic acid content ranges from 0.05 to 0.70 mg/ml and the ferulic acid from 0.01 to 1.39 mg/ml.